The Role of Social Media in the Formation of Collective Consciousness and Contemporary Social Movements - Maftuh Ihsan Nanda Kurniawan; Hully (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2025)
Social media has evolved into a new public space that influences the patterns of interaction, communication, and public participation in various social issues. This phenomenon shows that social media serves not only as a means of entertainment, but also as a strategic instrument in building collective awareness and organizing contemporary social movements. This article aims to analyze the role of social media in shaping public opinion, accelerating the dissemination of information, and mobilizing solidarity across geographical and cultural boundaries. This study uses a descriptive qualitative approach by analyzing literature, secondary data, and case studies of viral social movements on various digital platforms. The results of the analysis show that social media plays an important role in changing the pattern of community mobilization: from local actions to more inclusive global movements. However, its effectiveness is inseparable from challenges such as hoaxes, polarization of opinions, and the risk of algorithm manipulation. Therefore, the role of digital literacy and critical awareness is important so that social media truly becomes a medium that supports positive social transformation. This article concludes that social media is a new force in strengthening participatory democracy as well as a means to fight for social justice issues, provided that there is sound information management and responsible public participation.